Florida studies : selected papers from the 2012 and 2013 Annual Meetings of the Florida College English Association. - Reich, Paul D.; Leib, Andrew (Cambridge Scholars Publishing, 2014)
This volume contains a variety of essays about Florida literature and history by scholars from across the state representing every kind of institution of higher learning, from community colleges to small liberal arts institutions to large universities. The essays in the first section, 'Pedagogy', focus on the college classroom and the challenges facing institutions of higher learning in Florida. The essays in 'Old Florida' explore the state's varied and unique geographies. The final section ...